MODEL INTERAKSI BIRO PERJALANAN WISATA DENGAN PEMERINTAH KABUPATEN TORAJA UTARA - Matius Tinna Sarira; Muhammad Rusdi; Amirullah Amirullah; Masri Ridwan; Hasruddin Nur (Universitas Negeri Makassar, 2023)
This study aims to determine the form of interaction between travel agents in developing tourism travel products in North Toraja Regency. This study used descriptive qualitative method. Data collection techniques were carried out by means of observation, interviews and documentation. Based on the results of the study, it was found that the tourism potential in North Toraja Regency is very high, judging from the list of various attractions and the unique and distinctive characteristics that can only be found in North Toraja Regency. Existing tourism products are common tourism products and are a legacy from the design of existing tourism products since the opening of Toraja as a tourist destination. The tourism product produced by the travel agency is an arrangement of potential components in all regions in North Toraja Regency which are under the guidance of the Culture and Tourism Office as the government's representative. As for the forms of service and tourism cultural interaction with travel agents through Economic and Business Motivated Interaction, Culturally Motivated Interaction and Symbolic Interaction.Penelitian ini bertujuan untuk menegtahui bentuk interaksi biro perjalanan wisata dalam mengembangkan produk perjalanan wisata di Kabupaten Toraja Utara. Penelitian ini menggunakan metode deskriptif kualitiatif. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara dan dokumentasi. Berdasarkan hasil penelitian ditemukan bahwa potensi wisata di kabupaten Toraja Utara sangat tinggi dilihat dari daftar jumlah atraksi yang bervariasi dan karakter yang unik serta khas yang hanya bisa dijumpai di Kabupaten Toraja Utara. Produk wisata yang sudah ada merupakanproduk wisata yang umum dan menajdi warisan dari desain produk wisata yang sudah ada sejak dibukanya toraja menjadi destinasi wisata.produk wisata yang dihasilkan oleh biro perjalanan wisata adalah susunan komponen potensi disemua wilayah di Kabupaten Toraja Utara yang menjadi binaan Dinas Kebudayaan dan Pariwisata sebagai wakil pemerintah. Adapun bentuk Interaksi dinas kebudayaan dan pariwisata dengan biro perjalanan wisata melalui Interaksi Bermotif Ekonomi dan Bisnis, Interaksi Bermotif Budaya dan Interaksi Simbolis.